The Effect of Online Marketing and Shipping Costs on Consumer Buying Interest in Dennis Orchid House - Maria Renita Da Costa; Moch Nurhidayat; Warter Agustim (International Research & Development for Human Beings (IRDH), 2026)
This research explores how online promotion strategies and delivery charges impact consumer buying decisions at Dennis Orchid House, both individually and collectively. The study applies a quantitative descriptive approach, targeting buyers of Dennis Orchid House. A total of 100 participants were chosen using purposive sampling. Data were obtained through structured questionnaires. The responses were processed using multiple linear regression analysis, supported by t-tests for individual variables and an F-test for combined variable influence. The analysis shows that both online marketing and delivery fees have a positive influence on purchase interest, with an R² value of 0.756. This indicates that 75.6% of the variation in consumer interest is explained by the two variables. Statistical tests confirm that both factors significantly affect consumer buying interest, as shown by significance values below 0.05. Online marketing initiatives and delivery cost policies play an essential role in shaping customer purchasing decisions. Business owners are advised to enhance their digital marketing appeal and provide flexible shipping options to attract more buyers.